2016
DOI: 10.1002/jsfa.7764
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prebiotics ofAgave salmianafed to healthy Wistar rats

Abstract: Our data underline the advantage of targeting the gut microbiota by colonic nutrients like specific structure of fructans from A. salmiana, with their beneficial effects. More studies are necessary to define the role of fructans to develop more solid therapeutic solutions in humans. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…These studies were primarily designed to analyze the prebiotic effects from agave fructans in in vitro studies [1721], animal models [13, 22, 23] and clinical trials [2427], whereas other studies have investigated the effects on food intake, body weight gain and hyperglycemia [11, 14, 22, 28]. Only one study has been conducted to analyze liver steatosis in diabetic rats supplemented with agave fructans [12], and several studies have been designed to investigate the relationship between dp and biological activity [13, 20, 21].…”
Section: Resultsmentioning
confidence: 99%
“…These studies were primarily designed to analyze the prebiotic effects from agave fructans in in vitro studies [1721], animal models [13, 22, 23] and clinical trials [2427], whereas other studies have investigated the effects on food intake, body weight gain and hyperglycemia [11, 14, 22, 28]. Only one study has been conducted to analyze liver steatosis in diabetic rats supplemented with agave fructans [12], and several studies have been designed to investigate the relationship between dp and biological activity [13, 20, 21].…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have shown that beneficial bacterial additives, by changing the composition of the intestinal microflora and increasing the intestinal population of Lactobacillus, Bifidobacterium can help to lower cholesterol blood level [39][40][41]. Xie et al fed rats with a high cholesterol diet, Lactobacillus acidophilus M1-16 and Lactobacillus plantarum 9-41-A for 6 weeks.…”
Section: Dietary Influence On Hypercholesterolemic Ratsmentioning
confidence: 99%
“…and Bifidobacterium spp. 76 Shifts of colonic microbiota composition induced by pectins were not as prominent as shifts of cecal microbiota in the study conducted by Tian et al 105 In the cecal microbiota the rise in Lactobacillus was also present, specifically in groups receiving lowmethyl esterified citrus pectin and sugar beet pectin.…”
Section: Insight Into Rat Intestinal Microbiota Modulation By Food Sumentioning
confidence: 80%
“…and Bifidobacterium spp . (CFU g −1 ) in both test groups (approximately 4-log increase was observed in the group with symbiotic food) 76 Feruloylated oligosaccharides (FOs) from maize bran 45, male Sprague–Dawley rats, weighing 160–170 g n = 9, normal feed n = 9, + 300 mg/kg BW/d xylooligosaccharides (XOS) n = 9,+ 300 mg/kg BW/d XOS + 12 mg/kg BW/d ferulic acid (FA) n = 9, + 300 mg/kg BW/d FOs n = 9, + 600 mg/kg BW/d FOs Feces collected and stored at −80°C. 5 weeks DNA extraction using TIAN amp Stool DNA kit PCR amplification sequencing on the Illumina GAIIx platform reference base from Ribosomal Database Project Feruloylated oligosaccharides showed even higher prebiotic activity than XOS FOs : ↑bacterial richness and diversity ↓ ratio of Firmicutes to Bacteroidetes ↑ Bacteroidetes , Proteobacteria, Actinobacteria, Lactobacillus and Ruminococcus ↓ Clostridia 77 Pectins (four types) 40, male Wistar rats (300 ± 10 g) n = 8, control group n = 8, 3% (w/w) low-methyl esterified citrus pectin (LMP) n = 8, 3% (w/w) high-methyl esterified citrus pectin (HMP) n = 8, 3% (w/w) sugar beet pectin (SBP) n = 8, 3% (w/w) soy pectin (SSPS) Cecal and colonic digesta collected separately.…”
Section: Gut Microbiota Shifts In Healthy Rat Models By Different Nutmentioning
confidence: 89%